Recurrent NTM pulmonary disease despite avoidance of hot spring exposure in a plaque psoriasis patient treated with Secukinumab: a case report - Yixiao Wei; Chunlei Wang; Lingtao Chong; Xiaojing Cui (BMC Infectious Diseases)
Abstract Background Recurrent Non-Tuberculous Mycobacterial Pulmonary Disease (NTM-PD) related to treatment with Secukinumab has not been previously documented. Case presentation Despite adherence to treatment and avoiding hot springs, a plaque psoriasis patient experienced persistent NTM-PD relapses. Conclusions There is potential association between Secukinumab, an IL-17A inhibitor, and NTM disease, echoing anti-TNF biologics’ NTM risk, indicating the urgent need for further research on pathogenic mechanisms and risk factors.